Path dependent policymaking in the post-Brexit United Kingdom: what's new about the 'points-based' labour migration system?. Issue 3 (September 2022) - Dias-Abey, Manoj
Abstract: The end of free movement as a consequence of the United Kingdom (UK)'s withdrawal from the European Union (EU) meant that it was necessary for the UK to devise a new migration system when the transition period came to an end. One aim of this article is to determine in what respects the new system, which came into force on 1 January 2021, draws on or differs from the previous immigration system. To the extent that this inquiry reveals some similarities, another aim is to uncover how the policymaking process produced these continuities. Drawing on the concept of path dependency from the 'new institutionalism' literature, the analysis reveals that two critical decisions taken by the New Labour government (1997–2010) set in train a path dependent policy process that has shaped immigration law and policy today. Two mechanisms of path dependency are identified. First, there were continuities in the operation of conceptual frameworks, methodologies and conclusions amongst organisations tasked with designing the new immigration system. Second, the position adopted by employing enterprises favoured the retention of key features of the previous system.